Low Incidence of Antibodies to Recombinant Human Tissue-Type Plasminogen Activator in Treated Patients - Reed, B R; Chen, A B; Tanswell, P; Prince, W S; Wert, R M, Jr.; Glaesle-Schwarz, L; Grossbard, E B (Thrombosis and Haemostasis, 1990)
Sera from over 1,600 patients who received recombinant human tissue plasminogen activator (rt-PA) during clinical trials were assessed for the presence of antibodies to this therapeutic agent. The rt-PA was administered by a variety of dosage regimens for several different indications. Two different forms of rt-PA were used; one was a predominantly two chain form, and the other was a predominantly one chain form. A sensitive radioimmunoprecipitation assay was used to measure antibodies to rt-PA in patients’ serum before and after treatment. Of 932 patients tested with this assay, 929 were negative for antibodies to t-PA. Three patients developed low titers after treatment. Additional serum samples were obtained from these three patients within 2 years after rt-PA therapy and were negative for antibodies to t-PA. With the limited number of positive samples, no correlation could be found with dose or type of rt-PA, dosing regimen or clinical diagnosis. The virtual absence of antibody formation was confirmed in an additional 754 patients using a novel competitive two-site ELISA. It can be concluded that a single infusion of rt-PA was virtually unassociated with antibody formation, suggesting that repeat treatments could be given when necessary without the risk of immunologic complications as are seen with streptokinase or its derivatives.